The role of high pressure in preventing carbon contamination of transparent ceramics during spark plasma sintering. (15th March 2023) - Ratzker, Barak; Wagner, Avital; Kalabukhov, Sergey; Froumin, Natalya; Frage, Nachum
Abstract: Transparent ceramics sintered in the presence of graphite elements are susceptible to carbon contamination which causes severe transparency loss. Previous studies showed that applying high pressure during spark plasma sintering (SPS) can effectively prevent carbon contamination, but the underlying mechanism remained unclear. A common assumption is that the degree of carbon contamination depends on the CO/CO2 atmosphere sealed inside the closed porosity of sintered bodies and subsequent CO dissociation into CO2 and free carbon. In the present study, we combined sintering experiments on MgAl2 O4 and a thermodynamic analysis of the CCOCO2 system. It was concluded that the applied high pressure limits the amount of CO in two ways: early closure of pores at lower sintering temperatures and increasing the total gas pressure inside the mold – favoring stability of CO2 . This understanding enables better design of sintering processes of transparent ceramics in a carbon containing atmosphere. Graphical abstract: Image, graphical abstract